LIMITS OF PARLIAMENTARY IMMUNITY WITH REGARD TO GENDER VIOLENCE (REMUNOM, 2024)
AbstractThis article deals with the analysis of parliamentary immunity and its effects on gender-based violence. Parliamentary immunity is adopted in Brazil, as well as in many sovereign states. However, it is often used to derogate and subjugate minorities. The objective is to analyze aspects of parliamentary immunity in relation to gender-based violence. The research is important because one right cannot mitigate the other. Therefore, debate is necessary to better understand the topic and to find solutions to the problem. Thus, guiding the article, we seek the answer to how parliamentary immunity is related to gender-based violence? At the end of this research, it is possible to better understand how parliamentary immunity is related to issues of gender violence and how this scenario can be changed, based mainly on limits to parliamentary immunity as well as actions in all three powers to raise awareness about minorities and, actions that monitor existing laws so that they achieve their final objective. The methodology used to develop this scientific article was bibliographical research, extracting information from physical books, electronic books, scientific articles, monographs, magazines, and Brazilian court rulings on the subject, correlating them to the conclusion reached.